Combined Analysis of Pharmaceutical Active Ingredients and Transcriptomes of Glycyrrhiza uralensis Under PEG6000-Induced Drought Stress Revealed Glycyrrhizic Acid and Flavonoids Accumulation via JA-Mediated Signaling - Yao, Hua; Wang, Fei; Bi, Quan; Liu, Hailiang; Liu, Li; Xiao, Guanghui; Zhu, Jianbo; Shen, Haitao; Li, Hongbin (Frontiers in Plant Science, 2022)
Glycyrrhiza uralensis contains many secondary metabolites with a wide range of pharmacological activities. Drought stress acts as a positive regulator to stimulate the production of medicinal active component in G. uralensis, however, the underlying mechanism remains unclear. The aim of this work is to investigate the accumulation and regulatory mechanism of pharmaceutical active ingredients in G. uralensis under drought stress. The materials of the aerial and underground parts of G. uralensis seedlings treated by 10% PEG6000 for 0, 2, 6, 12, and 24 hours were used for RNA sequencing and determination of phytohormones and pharmaceutical active ingredients. PEG6000, ibuprofen (IBU), and jasmonic acid (JA) were utilized to treat G. uralensis seedlings for content detection and gene expression analysis. The results showed that, the contents of glycyrrhizic acid, glycyrrhetinic acid, and flavonoids (licochalcone A, glabridin, liquiritigenin, isoliquiritigenin, and liquiritin) were significantly accumulated in G. uralensis underground parts under drought stress. Kyoto Encyclopedia of Genes and Genomes analysis of the transcriptome data of drought-treated G. uralensis indicated that up-regulated differentially expressed genes (UDEGs) involved in glycyrrhizic acid synthesis in the underground parts and flavonoids synthesis in both aerial and underground parts were significantly enriched. Interestingly, the UDEGs participating in jasmonic acid (JA) signal transduction in both aerial and underground parts were discovered. In addition, JA content in both aerial and underground parts under drought stress showed the most significantly accumulated. And drought stress stimulated the contents of JA, glycyrrhizic acid, and flavonoids, coupled with the induced expressions of genes regulating the synthesis and transduction pathway. Moreover, In PEG6000- and JA-treated G. uralensis, significant accumulations of glycyrrhizic acid and flavonoids, and induced expressions of corresponding genes in these pathways, were observed, while, these increases were significantly blocked by JA signaling inhibitor IBU. JA content and expression levels of genes related to JA biosynthesis and signal transduction were also significantly increased by PEG treatment. Our study concludes that drought stress might promote the accumulation of pharmaceutical active ingredients via JA-mediated signaling pathway, and lay a foundation for improving the medicinal component of G. uralensis through genetic engineering technology.